An Origami-Based Soft Robotic Actuator for Upper Gastrointestinal Endoscopic Applications - Chauhan, Manish; Chandler, James H.; Jha, Animesh; Subramaniam, Venkataraman; Obstein, Keith L.; Valdastri, Pietro (Frontiers in Robotics and AI, 2021)
Soft pneumatic actuators have been explored for endoscopic applications, but challenges in fabricating complex geometry with desirable dimensions and compliance remain. Addition of an endoscopic camera or tool channel is generally not possible without a significant change in the diameter of the actuator. Radial expansion and ballooning of actuator walls during bending is undesirable for endoscopic applications. The inclusion of strain limiting methods like wound fibre, mesh or multi-material moulding have been explored, but the integration of these design approaches with endoscopic requirements drastically increases fabrication complexity, precluding reliable translation into functional endoscopes. For the first time in soft robotics, we present a multi-channel, single material elastomeric actuator with a fully corrugated design (inspired from origami); offering specific functionality for endoscopic applications. The features introduced in this design include (i) fabrication of multi-channel monolithic structure of 8.5 mm diameter, (ii) incorporation of the benefits of corrugated design in a single material (i.e. limited radial expansion and improved bending efficiency), (iii) design scalability (length and diameter), and (iv) incorporation of a central hollow channel for the inclusion of an endoscopic camera. Two variants of the actuator are fabricated which have different corrugated or origami length, i.e. 30 mm and 40 mm respectively). Each of the three actuator channels is evaluated under varying volumetric (0.5mls-1 and 1.5mls-1 feed rate) and pressurized control to achieve a similar bending profile with the maximum bending angle of 150o. With the intended use for single-use upper gastrointestinal endoscopic application, it is desirable to have linear relationships between actuation and angular position in soft pneumatic actuators with high bending response at low pressures; this is where the origami actuator offers contribution. The soft pneumatic actuator has been demonstrated to achieve a maximum bending angle of 200o when integrated with a manually driven endoscope. The simple 3-step fabrication technique produces a complex origami pattern in a soft robotic structure, which promotes low pressure bending through the opening of corrugation while retaining a small diameter and a central lumen, required for successful endoscope integration.